2012
DOI: 10.1007/s10763-012-9341-4
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Reflection of Inquiry Teaching in Finland Before and During an in-Service Program: Examination by a Progress Model of Collaborative Reflection

Abstract: ABSTRACT. In inquiry-based science education, there have been gradual shifts in research interests: the nature of scientific method, the debates on the effects of inquiry learning, and, recently, inquiry teaching. However, many in-service programs for inquiry teaching have reported inconsistent results due to the static view of classroom inquiries and due to the partial perspective between individual and collaborative reflections. Thus, by means of a theoretical progress model of collaborative reflection, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Inquiry-based learning defined as a process where students are involved in their learning, formulate questions, investigate widely and then build new understandings, meanings and knowledge and also understanding about how scientists learn the nature [12,13]. Inquiry has been regarded as an approach to bridge the gap between a scientist's way of doing science and a student's learning of science in school [14]. Inquiry-based learning can develop student's thinking and process skill [15].…”
Section: Introductionmentioning
confidence: 99%
“…Inquiry-based learning defined as a process where students are involved in their learning, formulate questions, investigate widely and then build new understandings, meanings and knowledge and also understanding about how scientists learn the nature [12,13]. Inquiry has been regarded as an approach to bridge the gap between a scientist's way of doing science and a student's learning of science in school [14]. Inquiry-based learning can develop student's thinking and process skill [15].…”
Section: Introductionmentioning
confidence: 99%
“…Supported reflection during preservice and in-service teacher education can lead to positive changes. Reflective professional development (PD) improved teachers’ abilities to identify underlying beliefs and specific needs for improvement (Kim, Lavonen, Juuti, Holbrook, & Rannikmäe, 2013). Preservice teachers who engaged in reflection, action research (Hagevik, Aydeniz, & Rowell, 2012), and portfolio reflection (Lyons, 1998) showed growth in inquiry toward their own practices.…”
Section: Relevant Researchmentioning
confidence: 99%
“…This process is an activity for students to improve their knowledge and understanding of scientific ideas and how scientists learn about the nature [10,11]. Inquiry has been regarded as an approach to bridge the gap between a scientist's way of doing science and a students' learning of science [12].…”
Section: Introductionmentioning
confidence: 99%